The subordinated debt alternative to Basel II - Herring, Richard J. (Journal of Financial Stability, 2004)
Basel II attempts to eliminate incentives for regulatory capital arbitrage and align capital regulation with best practices in credit risk management. Despite the imposition of very heavy compliance costs, it is unlikely to succeed in achieving either goal. This paper describes an alternative approach, based on mandatory issues of subordinated debt, which makes use of market discipline to achieve these goals at much lower cost.